Evaluation of Oxidative Stress and Using a Novel Automated Method For Measurement of Total Antioxidant Status in Preeclampsia - Kale, Ebru; Kale, Ahmet; Canoruç, Naime; Akdeniz, Nurten; Yalınkaya, Ahmet (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: The purpose of this study was to ev aluate total antioxidant status of preeclampsia with using a more recently developed automated measurement method and measurement of malondialdehy de (MDA) lev els as an oxidativ e stress marker in women with preeclampsia STUDY DESIGN: We perf ormed a case-control study consisting of randomly selected 50 healthy pregnant women and 50 patients diagnosed as preeclampsia. We measured the total plasma antioxidant capacity for all patients and oxidativ e stress was ev aluated with measurement of red blood cell malondialdehyde (MDA) lev els. RESULTS: The serum total antioxidant response (TAR) lev els were lower (1.29±0.33 TAR mmol Trolox eq/L) and the red blood cell malondialdehy de lev els of (MDA) were higher (7.1±0.4 nmol MDA/l) bef ore delivery (P<0.001) and these levels were not diff erent af ter delivery (six weeks later) in preeclampsia than control group (P>0.05). The serum total antioxidant response (TAR) levels significantly increased (1.55±0.49 mmol Trolox eq/L) and the malondialdehyde lev els signif icantly decreased (2.9±0,6 nmol MDA/l) in preeclamptic women af ter deliv ery when compared with the pre deliv ery levels CONCLUSIONS: Our findings suggest that preeclampsia is related with enhanced lipid peroxidation and decreased total antioxidant response before delivery and these parameters may be related at least partly to the pathogenesis of preeclampsia. Decreased lipid peroxidation and increased total antioxidant response after delivery may suggest recov ery of preeclampsia and using a simple, rapid and reliable automated method f acilitates to ev aluate and follow up of the lev els of oxidativ e stress in preeclampsia and this novel method may be used as a routine test in clinical practice while managing preeclampsia